Conical coupling angular stable plate fixation: a retrospective study - Rivera, Fabrizio; Maiello, Alessio; Maiello, Alessio; Pietro, Maniscalco; Di Stefano, Giovanni; Quattrini, Fabrizio (Acta Biomedica Atenei Parmensis, 2020)
Backgrounds. Conical coupling represents an alternative to screw coupling on angular stable plate fixation. Aims of the present study was to evaluate clinical effectiveness  and ease of plate removal of conical coupling locking plates into different scenario regarding quality of bone, type of fracture and operative technique. Methods. From May 2013 to December 2017, 198 patients with 206 fractures underwent open reduction and internal fixation with conical locking plate. In most cases fixation involved wrist (38%) and clavicle (24%) fractures but a varied type of fractures and bone were included in the study. Results. Ten complications related to plate fixation were observed (5,1%). Two case of intra-articular positioning of screws of wrist plate. One case of loss of reduction and breakage of wrist plate due to an inappropriate proximal fracture fixation.  Five cases of complications involved clavicle fixation: three cases of non-union, one case of peri-implant fracture, one screw loosening. One non-union of distal tibial fracture, one non-union in olecranon fracture were finally observed. Thirty-four patients that have symptoms that could be traceable to the implants in-situ underwent plate removal. No complications were observed during surgical plates removal. Conical coupling angular stability plate represents an actractive alternative to threaded angular stability plate.  Bush titanium insert, eliminating the problems of cold welding and cross-threading, simplifies surgical screws and plate removal